The Association Between Physical and Mental Health and Face Mask Use During the COVID-19 Pandemic: A Comparison of Two Countries With Different Views and Practices - Wang, Cuiyan; Chudzicka-Czupała, Agata; Grabowski, Damian; Pan, Riyu; Adamus, Katarzyna; Wan, Xiaoyang; Hetnał, Mateusz; Tan, Yilin; Olszewska-Guizzo, Agnieszka; Xu, Linkang; McIntyre, Roger S.; Quek, Jessica; et al. (Frontiers in Psychiatry, 2020)
Background: The physical and mental health of citizens living in a country that encouraged face masks (China) and discouraged face masks (Poland) during the initial stage of the COVID-19 pandemic remained unknown. We conducted a cross-country study to compare the psychological impact of the COVID-19 pandemic on Poles and Chinese. This study aimed to compare the levels of psychological impact of pandemic and levels of anxiety and depression between China and Poland. Methods: The survey collected information on demographic data, physical symptoms, contact history, and precautionary measures. The psychological impact was assessed using the Impact of Event Scale-Revised (IES-R), and mental health status was assessed by the Depression, Anxiety and Stress Scale (DASS-21). The chi-squared test was used to analyze the differences in categorical variables between the two populations. Linear regression was used to calculate the bivariate associations between independents variables (e.g. physical symptoms, precautionary measures) and dependent variables (e.g. mental health outcomes). Results: This study included a total of 2266 respondents from both countries (1056 Poles, 1210 Chinese). There were significantly less Polish respondents who wore face masks (Poles: 35.0%, Chinese: 96.8% p<0.001). Significantly more Polish respondents reported physical symptoms resembling COVID-19 infection (p<0.001), recent medical consultation (p<0.01), recent COVID-19 testing (p<0.001) and hospitalization (p<0.01). Furthermore, Polish respondents had significantly higher levels of anxiety, depression and stress (p<0.001) than Chinese. The mean IES-R scores of Poland and China were above the cut-off for post-traumatic stress disorder (PTSD) symptoms. Besides precautionary measures, unemployment, retirement, physical symptoms resembling COVID-19 infection, recent medical consultation or COVID-19 testing and long daily duration of home confinement were risk factors for PTSD symptoms, anxiety, depression or stress for Polish respondents. Conclusion: Use of face masks at the community level may safeguard better physical and mental health during the COVID-19 pandemic. There is a need of health education with scientific information from Polish health authority on the proper use of face masks and reduce social stigma. This study was limited by the respondent sampling method that had compromised the representativeness of samples.